THE RISE OF INTERNET BANKING: OPPORTUNITIES AND CHALLENGES IN THE DIGITAL ERA - Kaur, Karmjeet; Parveen Lata; Bhalla, Sahil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India and its people are changing very quickly due to the digital age. Every day, technology offers more and more chances for people to become empowered and, as a result, to develop continuously. The technology revolution has affected every industry. India's banking sector, which is regarded as the foundation of any economy, has long been run using conventional methods (BHARGAVA, A. 2017). Automated teller machines were used to improve electronic banking, which then evolved into online banking. Customers can manage their accounts and conduct financial transactions via electronic banking from a computer or smartphone. Bill payment, electronic transfers, debit and credit cards, mobile banking, telebanking, and similar services are among the services that banks offer ( Nithya, C.) . This paper focuses on different methods in payment system in online Banking Services and check the growth in using these methods. The data is collected from secondary sources. It aims to explore the ways in which technology has changed the banking industry and various opportunities and challenges faced by banking industry.